Menciptakan Kepuasan Konsumen pada Jasa Servis Motor Berdasarkan Persepsi Pelanggan Bengkel Ikky Costum - Fakhruddin Fakhruddin (Jurnal Manajemen Riset Inovasi, 2026)
This study aims to analyze the quality of motorcycle service services based on customer perception of the SERVQUAL model which consists of five main dimensions, namely reliability, responsiveness, assurance, tangibles, and empathy at the Ikky Costum Workshop in Samarinda using a qualitative approach. Data was obtained through observation, interviews, and documentation involving owners, mechanics and customers. Data analysis in this study uses interactive analysis techniques which include data reduction, data presentation, and conclusion drawn. The results of the study show that the quality of service in general meets customer expectations, especially in terms of service speed, friendly attitude and the ability to provide explanations to customers even though it is not fully optimal. However, there are still obstacles such as the limited number of mechanics, lack of service consistency, and lack of optimal time management. Workshop facilities are considered adequate to support customer comfort even though they still need improvement. Therefore, improving mechanical competence through periodic technical training, increasing the number of workers to improve service efficiency and improving the service management system to be more structured and consistent. In addition, workshops need to improve the quality of facilities such as the comfort of the waiting room and the arrangement of equipment as well as maintain a friendly attitude and attention to customers in order to create customer satisfaction and loyalty in the long term. Improving service quality needs to be done comprehensively to increase customer satisfaction and loyalty.